From Sport s Collectibles to the Digital Humanities: the Evolution of Technology and the Transformation of Consciousness - Baraldi, Luca (Archeomatica, 2024)
For several decades now, we have been living through rapidly accelerating technological change, at a moment in history in which digitization is remaking the relationship between knowledge and humanity. Until recently, the act of passing down our history from generation to generation was entrusted to the voluntary or involuntary production of material witnesses. But in today’s growing digital ecosystem, historical memory has turned into data, computer architectures, and algorithmic interpretations. It is important not to approach this in purely technological terms, but instead as a real epistemological revolution. This not only changes the way we do things; it is also changing the ways we perceive them, know them, interpret them, and rework them. History, culture, and knowledge are all part of an evolving information ecosystem, which today, more than ever, is based on the possibility of direct interaction, immediate accessibility, and dynamic modularity. All of this requires new skills and new methodologies, born from an encounter between humanistic knowledge and technology.